Calreticulin Protects Rat Microvascular Endothelial Cells against Microwave Radiation‐induced Injury by Attenuating Endoplasmic Reticulum Stress. (August 2014) - Li, Wei‐Hong; Li, Yu‐Zhen; Song, Dan‐Dan; Wang, Xiao‐Reng; Liu, Mi; Wu, Xu‐Dong; Liu, Xiu‐Hua
Abstract Objective This study was designed to evaluate whether exogenous CRT was beneficial for alleviating MR‐induced injury by suppressing ER stress in rat MMECs. Methods MMECs were pretreated with CRT (25 pg/mL) for 12 hours, followed by the exposure to 2.856 GHz radiation at a mean power density of 30 mW/cm2 for six minutes. MR‐induced injury in MMECs was evaluated by LDH leakage, apoptosis, and cell viability analysis. The expression of GRP78, CRT, CHOP, Bcl‐2, and Bax were examined by Western blot analysis to reflect ER stress response and ER stress‐related apoptosis. Results MR induced marked MMECs injury, as shown by increased LDH leakage and apoptosis rate and decreased cell viability. MR also induced excessive ER stress, characterized by increased expression of GRP78 and CRT, and ER stress‐related apoptotic signaling as well, as shown by the upregulation of CHOP and Bax and the downregulation of Bcl‐2. Exogenous CRT pretreatment remarkably attenuated MR‐induced cell apoptosis and LDH leakage, ER stress, and activation of the ER stress‐related apoptotic signaling. Conclusions Exogenous CRT attenuates MR‐induced ER stress‐related apoptosis by suppressing CHOP‐mediated apoptotic signaling pathways in MMECs.